Effect of Adding Caffeine in Tris Extender on Critical Quality Parameters of Cryopreserved Surti Buck Semen - Bhut, Darshita V; Khasatiya, Chandubhai T; Singh, Virendra Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was conducted to evaluate the effect of adding caffeine in Tris egg yolk citrate glycerol (TEYCG) extender on critical quality  parameters of cryopreserved Surti buck semen. Four mature Surti bucks (aged >1 year) were selected. Total 64 ejaculates were collected  @ 2 ejaculates per week/buck over eight weeks period. At every collection, ejaculates of all 4 bucks were pooled and divided into four  equal aliquots, diluted with TEYCG extender (having 100 x106 sperms/mL), added with caffeine as 0 mM (T1, control), 1 mM (T2), 3 mM  (T3) and 5 mM (T4) in the four aliquots, respectively, and were cryopreserved and stored for 24 h in LN2. Individual sperm motility,  viability, morphology and functional membrane integrity of sperms were evaluated at initial, pre-freeze (after equilibration for about 4  h at 4°C) and post-thaw stages. Individual motility, viability, morphologically normal and HOST-reacted sperms decreased significantly  (p
Keywords: Caffeine; Cryopreservation; Semen quality; Surti buck.